Hubungan Karakteristik Pasien Diabetes Melitus Tipe 2 dengan Gangguan Fungsi Kognitif di Puskesmas Andalas - Khairy, Faldi Arkan; Firdawati, Firdawati; Liza, Rini Gusya; Rasyid, Rosfita; Julizar, Julizar (Faculty of Medicine, Universitas Andalas, 2025)
Type 2 Diabetes Mellitus (T2DM) is a metabolic disease that can cause various complications, one of which is cognitive dysfunction. Specific characteristics in T2DM patients can be risk factors for cognitive dysfunction, such as sex, age, employment status, education level, duration of diagnosis, comorbidity status, and degree of treatment adherence. Objective: To determine the association between the characteristics of Type 2 DM patients and cognitive dysfunction. Methods: This study used an observational analytical method with a cross-sectional study design conducted on 104 Type 2 DM patients at the Andalas Community Health Center, Padang, who met the inclusion and exclusion criteria. This study utilized the Montreal Cognitive Assessment-Indonesia (MoCA-Indonesia) questionnaire to evaluate the cognitive level of patients. This study was conducted from January to October 2024. Results: The Chi-square test showed a significant association between employment status (p = 0.038) and education level (p = 0.046) and cognitive dysfunction. Meanwhile, there is no significant association between sex (p = 1.000), age (p = 0.456), duration of diagnosis (p = 1.000), comorbidity status (p = 1.000), and degree of treatment adherence (p = 0.188) with cognitive dysfunction. Conclusion: Employment status and education level are significantly associated with cognitive impairment. Keywords: cognitive dysfunction, T2DM, patient characteristics